(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
On 17 September 2007, the Court of First Instance acknowledged, as the European Commission had three years ago, the existence of two separate abuses byMicrosoft; (i) refusal to supply, and (ii) tying. With respect to the first, both the European Commission and the Court concluded that Microsoft had abusively refused to supply its competitors with its intellectual property rights. This article focuseson the leght intersection between Intellectual Property Law and Competition in the framework of compulsory licensing. It indicates potgraf problems arising prous competition in markets foundied by innovation, as well as the role played in these sectors by the essential facilities doctrine. Finally, the article offers a series of conclusions.